COMPANY VALUE IMPROVEMENT THROUGH FUNDING POLICY BASED ON OWNERSHIP STRUCTURE (COMPARISON STUDY AT CONVENTIONAL AND SHARIA MANUFACTURING COMPANIES) - Jumaizi, Jumaizi; Ngaijan, Ngaijan (IJIBE (International Journal of Islamic Business Ethics), 2019)
This research aims to discuss and analyze the influence of ownership structure on the value of the company by dividend policies. The companies analyzed in this research were manufacturing companies listed on Indonesia Stock Exchange (IDX). Data that has been collected is analyzed using Multiple Regression. The results showed that managerial ownership and institutional ownership have a negative and significant impact toward debt policy and company value, while debt policy has a positive and significant impact toward firm value. This phenomenon shows that both shareholders of management and institutional shareholders consider debt policy endanger their position in the company, and will not be materially profitable. Meanwhile, the debt policy is considered as a positive signal of the existence of a business project that the company works on, because the company needs a lot of funds. On the other hand, the ownership composition of shares dominated by management and institutional shareholders is seen as a threat in the community, because there are opportunities to benefit themselves but will not benefit the community. In the end, information asymmetry is still a problem between individual and small shareholders, with shareholders who are able to obtain important company information such as institutional shareholders and shareholders who also control the company's management.